Late Paleozoic Tectonic Evolution of the Paleo‐Asian Ocean in the Northern Alxa Block (NW China). Issue 8 (14th August 2020) - Tian, Rongsong; Xie, Guoai; Zhu, Wenbin; Zhang, Jin; Gao, Shuang; Zhang, Beihang; Zhao, Heng; Li, Tian
Abstract: The northern Alxa Block occupies a key position in the southern margin of the Central Asian Orogenic Belt (CAOB) and records late Paleozoic subduction and closure processes of the Paleo‐Asian Ocean (PAO). However, there are still controversies regarding the timing and location of the final closure of the PAO. This study presents structural deformation data and geochronological and geochemical data for Permian volcanic rocks, as well as detrital zircon provenance analysis of Permian sedimentary rocks along the Nuoergong‐Langshan Zone (NLZ) in the northern Alxa Block. During the early to middle Permian, the PAO lithospheric slab subducted beneath the northern Alxa Block, rendering a continental volcanic arc in the NLZ and also giving rise to extensive folding, thrusting, and crustal thickening. The crustal thickening in the NLZ may trigger the early Permian magmatic flare‐up that constructed much of the continental arc plutons. In the middle to late Permian, a retroarc foreland basin was formed, within which the Dahongshan Formation deposited. Significant active tectonic movements led to regional unconformity occurring during this period. A large‐scale dextral ductile shear deformation in the NLZ resulting from the lateral extrusion of the thickened crust after the terminal amalgamation of the southern CAOB was constrained between 272 and 249 Ma, suggesting a late Permian tectonic transition from compression to transpression. Combining these findings with published data, we suggest that the final consumption of the PAO occurred in the late Permian, probably along the Enger Us suture zone in the northern margin Alxa Block. Key Points: Early and middle Permian subduction and crustal thickening processes existed along the Nuoergong‐Langshan Zone (NLZ) The Permian subduction‐related tectonic configuration of magmatic arc, fold‐thrust belt, and retroarc foreland basin system developed in the NLZ A synthetical late Paleozoic tectonic scenario has been proposed in the middle segment of the southern Central Asian Orogenic Belt